Michelia doltsopa x figo 'Allspice' Allspice Banana Shrub - Edward Gilman (EDIS, 2007)
This document provides a detailed description of the Allspice Banana Shrub (Michelia doltsopa x figo ‘Allspice’), an evergreen shrub known for its dense, upright growth and fragrant, magnolia-like flowers. It outlines the plant’s physical characteristics, including its height, spread, leaf arrangement, and flower color. The document also covers the shrub’s preferred growing conditions, such as soil type, light requirements, and drought tolerance. Additionally, it discusses the plant’s uses in landscaping, its propagation methods, and potential pest issues. The Allspice Banana Shrub is noted for its ornamental features and suitability for urban environments. Original publication date October 1999.